Vertical Mixing in The Onshore Region of The Northwestern Maluku Sea, Indonesia - Priyono, Bayu; Purwandana, Adi; Kusmanto, Edi; Nuratmojo, Nuratmojo; Muhadjirin, Muhadjirin (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2023)
Spatio-temporal dynamics of vertical mixing in the northwestern Maluku Sea were quantified using the Thorpe Method from archived CTD datasets collected during the expedition of Baruna Jaya VIII RCO-LIPI on November 12–13, 2000. The turbulent kinetic energy (TKE) dissipation rate and vertical eddy diffusivity values inspected the variability of mixing properties. Higher values for both parameters were found at the shallower bathymetry, which is less than 1000 m deep. This suggests that the water column is vertically unstable as a result of being often subjected to internal solitary wave (ISW) breaking events. The strong temporal variability observed from the density profile also indicated a strong impact on internal tide activity. There was temporal fluctuation of the TKE dissipation rate as well as vertical eddy diffusivity values following semidiurnal periodicity, with typical variability up to one order of magnitude for both the dissipation and diffusivity. The range of fluctuation is [6.8×10-8 ? 9.3×10-7] W kg-1 and [1.5×10-5 – 5.4×10-3] m2s-1, respectively in the upper 200 m depth. This water generated a high dissipation rate and vertical diffusivity when regularly exposed to internal solitary waves breaking from the Lifamatola Passage.Keywords: mixing properties, CTD data, turbulent kinetic energy, vertical eddy diffusivity